Citric-acid preacidification enhanced electrokinetic remediation for removal of chromium from chromium-residue-contaminated soil. Issue 3 (1st February 2018) - Meng, Fansheng; Xue, Hao; Wang, Yeyao; Zheng, Binghui; Wang, Juling
ABSTRACT: Electrokinetic experiments were conducted on chromium-residue-contaminated soils collected from a chemical plant in China. Acidification-electrokinetic remediation technology was proposed in order to solve the problem of removing inefficient with ordinary electrokinetic. The results showed that electrokinetic remediation removal efficiency of chromium from chromium-contaminated soil was significantly enhanced with acidizing pretreatment. The total chromium [Cr(T)] and hexavalent chromium [Cr(VI)] removal rate of the group acidized by citric acid (0.9 mol/L) for 5 days was increased from 6.23% and 19.01% in the acid-free experiments to 26.97% and 77.66% in the acidification-treated experiments, respectively. In addition, part of chromium with the state of carbonate-combined will be converted into water-soluble state through acidification to improve the removal efficiency. Within the appropriate concentration range, the higher concentration of acid was, the more chromium was released. So the removal efficiency of chromium depended on the acid concentration. The citric acid is also a kind of complexing agent, which produced complexation with Cr that was released by the electrokinetic treatment and then enhanced the removal efficiency. The major speciation of chromium that was removed from soils by acidification-electrokinetics remediation was acid-soluble speciation, revivification speciation and oxidation speciation, which reduced biological availability of chromium.